New data on the clearwing moth fauna of the Altai Mountains, Russia, with the description of two new species (Lepidoptera, Sesiidae) - Gorbunov, Oleg G. (Zootaxa, 2018)
The clearwing moth fauna of the Altai Mountains, Russia is reviewed. Two new species Synanthedon altaica sp. nov. and Bembecia aktashica sp. nov. are described and illustrated. Synanthedon polaris (Staudinger, 1877) is recorded as new for the region. New information on the bionomics and distribution of Dipchasphecia altaica O. Gorbunov, 1991 is provided.